An epidemiological and etiological analysis of 5026 peripheral nerve lesions from a European level I trauma center - Aman, Martin; Zimmermann, Kim S.; Thielen, Mirjam; Thomas, Benjamin; Däschler, Simeon C.; Böcker, Arne Hendrik; Stolle, Annette M.; Bigdeli, Amir Khosrow; Kneser, Ulrich; Harhaus-Wähner, Leila (Journal of Personalized Medicine, 2022)
Background: Peripheral nerve lesions are associated with debilitating long-term consequences. Albeit being essential for evidence-based clinical decision making, epidemiological and etiological data are scarce. We therefore aimed to comprehensively analyze epidemiological and etiological factors of peripheral nerve lesions in one of the largest cohorts. Methods: We screened a total of 110,667 patients treated at our level I trauma center between January 2012 and July 2020 for nerve lesions. Subsequently, demographics, etiologies, concomitant injuries, and lesion characteristics were analyzed. Results: A total of 5026 patients, predominantly young males suffering from non-work-related nerve injuries, were treated. Proximal levels of injury were more likely to be accompanied by fractures, whereas more distal injuries with concomitant vessel or tendon injury. Main causes were 54.6% lacerations. Acute traumatic nerve injury was treated within 24 h in 55.9% of cases. Conclusions: Given the young age of affected patients, early diagnosis and treatment in specialized centers may facilitate their early return to work and improve long-term functional outcomes. The data show the importance of a special attention on nerve injuries, which may be masked by large accompanying injuries. New findings on lesion characteristics of selected subgroups and accompanying circumstances can support a change in treatment strategies.
Gesehen am 21.12.2022